Relationship Parity and Contraception with Mild Preeclampsia at Puskesmas Jagir - Rizky Pradana Setiawan (Jurnal Berkala Epidemiologi, 2016)
Most cases of mild preeclampsia were found in the Public health center (PHC) of Jagir in 2011-2014. Every year there is a significant increase in the number of cases of mild preeclampsia in PHC of Jagir. The purpose of this study was to analyze the relationship between characteristics, family history, and administration of calcium supplementation in pregnant women with mild preeclampsia at the PHC of Jagir in Surabaya. This research is non-reactive research with case-control study design. This study uses secondary data from the PHC of Jagir in 2014, namely maternal and child health card and the cohort of pregnant women. Sampling using a simple random sampling technique. The variables studied were age, weight change, parity, family history of preeclampsia, contraception, family history of diabetes mellitus, family history of chronic hypertension, and administration of calcium supplementation. The statistical test used was the Chi-square test. The results showed significant variables with preeclampsia were parity (p = 0.001; OR 0.17) and contraception (p = 0.019; OR = 5.636). There is a relationship between parity and contraception with the occurrence of mild preeclampsia in PHC of Jagir. Health workers are expected to provide Education Information Communication (IEC) about ideal body mass status before pregnancy, parity, contraception, and weight changes during pregnancy.